2020
DOI: 10.1177/0733464820959163
|View full text |Cite
|
Sign up to set email alerts
|

Responding to a COVID-19 Outbreak at a Long-Term Care Facility

Abstract: This article describes an outbreak of COVID-19 in a long-term care facility (LTCF) in West Virginia that was the epicenter of the state’s pandemic. Beginning with the index case, we describe the sequential order of procedures undertaken by the facility including testing, infection control, treatment, and communication with facility residents, staff, and family members. We also describe the lessons learned during the process and provide recommendations for handling an outbreak at other LTCFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 5 publications
2
49
0
Order By: Relevance
“…Family members explicitly argued that the absence of physical contact resulted in severe emotional consequences both for them and for their loved ones. This finding adds to research conducted elsewhere (Shrader et al, 2021), which stresses the important emotional bond between family members and older persons, even in the context of LTC settings during the pandemic (Verbeek et al, 2020). It also stresses the fact that technology does not provide an adequate replacement to actual physical and emotional contact.…”
Section: Discussionsupporting
confidence: 58%
“…Family members explicitly argued that the absence of physical contact resulted in severe emotional consequences both for them and for their loved ones. This finding adds to research conducted elsewhere (Shrader et al, 2021), which stresses the important emotional bond between family members and older persons, even in the context of LTC settings during the pandemic (Verbeek et al, 2020). It also stresses the fact that technology does not provide an adequate replacement to actual physical and emotional contact.…”
Section: Discussionsupporting
confidence: 58%
“…The studies were all observational in nature. [ [11] , [12] , [13] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ] All of the studies reported RT-PCR-confirmed COVID-19 cases amongst the residents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The concerns of staff underscore the importance of proper training and disseminating updated information on the novel virus as a key strategy toward adequate preparedness. [ 27 , 46 , 60 ] Provision of universal paid sick leave, additional financial incentives during a crisis situation, professional development resources, and opportunities for new skill acquisition may encourage staff availability during such global challenges. [47] …”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies also reported that the COVID-19 virus dispersed and remained viable in the air sample of enclosed hospital wards 38 , 39 . Besides, a huge number of cases reported that indoor crowded and inadequately ventilated settings such as choir practice 40 , 41 , densely populated sports facilities 42 , nursing home 43 also caused COVID-19 infection clusters. Therefore, preventing human gathering and contact is the most efficient way to slow down the spreading of the virus.…”
Section: Transmission Of Covid-19mentioning
confidence: 99%